2019
DOI: 10.1039/c9sc01754b
|View full text |Cite
|
Sign up to set email alerts
|

Unusual confinement properties of a water insoluble small peptide hydrogel

Abstract: A water insoluble peptide-hydrogel that shows unique compartmentalization by not allowing any exchange to and from the hydrogel and can protect enzymes from denaturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 50 publications
(60 reference statements)
1
56
0
Order By: Relevance
“…Incorporation of the hydrophobic tail at one end of the NDI moiety ensures that the peptide sequences remain face to face as NDI and Py units form CT complexes (Scheme 1A). Amongst all these pairs, PyKC 32 and NDI-1 (Scheme 1 and S3 †) were found to have the closest proximity of the -SH groups (4.07Å, Fig. 1, S1 and Table S2 †) in the energy minimized structures of the pairs as obtained from DFT calculations.…”
Section: Resultsmentioning
confidence: 94%
“…Incorporation of the hydrophobic tail at one end of the NDI moiety ensures that the peptide sequences remain face to face as NDI and Py units form CT complexes (Scheme 1A). Amongst all these pairs, PyKC 32 and NDI-1 (Scheme 1 and S3 †) were found to have the closest proximity of the -SH groups (4.07Å, Fig. 1, S1 and Table S2 †) in the energy minimized structures of the pairs as obtained from DFT calculations.…”
Section: Resultsmentioning
confidence: 94%
“…The developed hydrogelators could retain enormous quantity of water in their structure and form elastic gels which slowly biodegrades into smaller molecules due to proteolysis or hydrolysis. 26 The drug release study results revealed the initial burst release of MP which might be due to physical entrapments of MP, followed by sustain release profile. 27 The results could be attributed to the initial release of MP from the solution of 1P + MP which later self-assembled in presence of ALP entrapping the drug in hydrogel.…”
Section: Discussionmentioning
confidence: 95%
“…A series of characterization studies were performed to examine and compare the properties of the composite hydrogels to those of hydrogels prepared with the polymers alone or only with PyKC. PyKC forms disulfide linked dimers in neutral to basic conditions due to the presence of cysteine residue in the sequence [ 34 ]. These dimers have been previously shown to be crucial for the hydrogelation of PyKC [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…PyKC forms disulfide linked dimers in neutral to basic conditions due to the presence of cysteine residue in the sequence [ 34 ]. These dimers have been previously shown to be crucial for the hydrogelation of PyKC [ 34 ]. ESI-MS analyses of 24 h matured samples of HA/PyKC and Gel/PyKC composite hydrogels showed the presence of a peak corresponding to the PyKC dimer ( Figures S1 and S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation